The Influence of Theatrical Mysteries on the Sienese Art of the First Half of the 15th Century: The Example of Sassetta’s Works - Kolpashnikova, Daria D. (Actual Problems of Theory and History of Art, 2019)
Theatrical performances that accompanied important Church festivals have been an integral part of European culture since the early Middle Ages. Their scenography and machinery, interpretation of subjects, decorative design had a significant impact on the development of Renaissance painting. This article considers the impact of images of religious mysteries on the altar painting of the first half of the Quattrocento on the example of the works created by a Sienese artist Stefano di Giovanni da Cortona (Sassetta). Siena was one of the Tuscan centers of the Renaissance that were especially active in the maintenance and decoration of feasts, including those associated with the celebration of recently canonized local saints (St. Bernardine, later St. Catherine of Siena). The Gothic style of Sassetta allowed the artist to figuratively and expressively interpret the impressions that he could get while watching one of the religious mysteries: the choir singing, actors’ movements, the machinery of the feast. Among Sassetta’s works which traced the influence of early Renaissance theatrical performances are a fragment of the altar of the Eucharist with the image of St. Anthony, images of the Ascension of the Virgin, the central panel of the San Sepolcro altarpiece dedicated to St. Francis.
Keywords: Siena; Quattrocento; Sassetta; theatrical performances; religious festivals; theatre; Renaissance painting